Agronomic Management for Improving the Water Productivity under Sri Ram Sagar Project Command, Andhra Pradesh, India - Kumar, K. Avil; Kalpana, D.; Reddy, M. Devender (International Journal of Bio-resource and Stress Management, 2023)
On-farm trials (OFT) to assess the water productivity and to suggest alternative agronomic measures for its improvement during 2008-09 and 2009-10 were conducted under D51 distributory of Kakatiya Canal, Sri Ram Sagar Project, Andhra Pradesh. The grain yield and field water use productivity improved by adoption of ridge and furrow method of irrigation in place of flat bed for maize, rotational irrigation/alternate wetting and drying and by maintaining 44 hills m-2 in rice during rabi. Adopting these agronomic techniques there will be a saving of 122-162 mm of water in maize and 8-12% water in rice over farmer’s practice of flat bed in maize and daily irrigation (continuous submergence of 5-10 cm), respectively. Further, application of higher levels of N than recommended has improved grain yield of rice and thereby field water use efficiency. Application of 90 kg N ha-1 improved yield and water productivity of sesame. The irrigation rate (quantity of water) applied was more under canal irrigation compared to well irrigation. Farmers adjusted their cropping pattern by crop diversification from rice to green gram and ground nut and used we1l water in conjunction with rain and canal when water scarcity observed during 2009-10 compared to 2008-09 under D51 canal command area of Sri Ram Sagar Project.